Cloning a lysine-rich protein gene from potato (Solanum tuberosum L.) cultivar Thuong Tin and construction of the expression vector - Luong, Tran Thi; Ninh, Nguyen Thuy; Thanh, Nguyen Duc (Academia Journal of Biology, 2017)
Lysine is one of the limiting essential amino acids because it is not synthesized in the body of animals and humans. They must obtain lysine from their diet. Recent results of gene transfer research showed the possibility of overexpression of genes encoding natural lysine-rich proteins in crops such as rice and corn, to improve protein quality by increasing the lysine content. However, there has been little report on cloning genes for lysine-rich proteins. In this article, we present the results of cloning the StTTLP gene encoding a lysine-rich protein from Thuong Tin potato cultivar. After successful cloning, we have constructed an expression vector to be used for gene transfer. The cloned gene had similarities of 94% and 99% to the SBgLR sequences that were registered in GenBank with the accession numbers KU987257.1 and AY377987.1, respectively.  The deduced amino acid sequence of StTTLP protein has high lysine proportion of 16.9%. In addition, glutamic acid component was also high with  the value of 22.8%. Thus, the cloned gene is considered as the gene encoding a lysine- and glutamic acid-rich protein. StTTLP gene was successfully cloned into the plant expression vector pCAMBIA2300 under the control of globulin 1 promoter (Glo1) from maize. These results provide a useful tool for gene engineering to improve the quality of protein in crop plants.